25. RESULTS OF USING THE HEARING SCREENING QUESTIONNAIRE ON THE ELDERLY WITH SUDDEN HEARING LOSS AT VIETTIEP FRIENDSHIP HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the results of hearing screening on patients with sudden hearing loss using the HHIE-S at Viet Tiep Friendship Hospital in 2024.Objects and methods: A cross-sectional study was conducted on 101 patients with sudden hearing loss at Viet Tiep Friendship Hospital, Hai Phong city from August 2024 to December 2024. The elderly patients were examined by pure tone assessment, and interviewed using the HHIE-S.Results: 100% of the elderly with sudden hearing loss through pure tone assessment were classified as having moderate or higher hearing loss. However, when using the HHIE-S questionnaire, the study subjects tended to overestimate the severity of hearing loss. While using the questionnaire, up to 95% of the study subjects had severe hearing loss, the pure tone assessment results classified only 47.5% of the subjects as having severe or higher hearing loss and 50.5% of the subjects as having moderate hearing loss.Conclusion: The HHIE-S questionnaire can be used to screen for hearing loss in the elderly with sudden hearing loss. The questionnaire should be validated for use in assessing the severity of hearing loss in the elderly with or without signs of hearing loss in the community or medical facilities.
Keywords: Hearing loss; screening; HHIE-S; Viet Tiep Friendship Hospital